2021
DOI: 10.3390/en14185847
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Hydrogen Household Energy Systems Including Incentives on Energy Communities and Externalities: A Case Study in Italy

Abstract: The building sector is one of the key energy consumers worldwide. Fuel cell micro-Cogeneration Heat and Power systems for residential and small commercial applications are proposed as one of the most promising innovations contributing to the transition towards a sustainable energy infrastructure. For the application and the diffusion of these systems, in addition to their environmental performance, it is necessary, however, to evaluate their economic feasibility. In this paper a life cycle assessment of a fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the other hand, Mayyas et al [64] demonstrated that renewable energy from large scale power hubs serving industrial consumers can be stored in the form of hydrogen with a competitive levelized cost of hydrogen production and levelized cost of energy storage in the United States, to be sold later as a fuel for FCEVs or converted back into electricity. As far as energy communities are concerned, Caramanico et al [65] performed a life cycle assessment of the application of a fuel cell/photovoltaic hybrid micro-cogeneration heat and power system for a residential building with a detailed economic analysis, showing that annual savings can be obtained, but due to the high capital costs, some kind of incentives are needed to foster the deployment of such technologies. Liu et al [66] modelled the planning of a distributed hydrogen-based MES and applied it to twelve typical cities around the world with different energy demand profiles and solar radiation, finding that this application can significantly reduce the operation cost of the energy system, except in high cooling demand and low solar radiation regions.…”
Section: Hydrogen In the Energy Hub Contextmentioning
confidence: 99%
“…On the other hand, Mayyas et al [64] demonstrated that renewable energy from large scale power hubs serving industrial consumers can be stored in the form of hydrogen with a competitive levelized cost of hydrogen production and levelized cost of energy storage in the United States, to be sold later as a fuel for FCEVs or converted back into electricity. As far as energy communities are concerned, Caramanico et al [65] performed a life cycle assessment of the application of a fuel cell/photovoltaic hybrid micro-cogeneration heat and power system for a residential building with a detailed economic analysis, showing that annual savings can be obtained, but due to the high capital costs, some kind of incentives are needed to foster the deployment of such technologies. Liu et al [66] modelled the planning of a distributed hydrogen-based MES and applied it to twelve typical cities around the world with different energy demand profiles and solar radiation, finding that this application can significantly reduce the operation cost of the energy system, except in high cooling demand and low solar radiation regions.…”
Section: Hydrogen In the Energy Hub Contextmentioning
confidence: 99%
“…The LCA methodology is commonly used to quantify system efficiency in terms of thermal efficiency, water used, and associated externalities, such as carbon emissions [18,19]. A full LCA requires: 1.…”
Section: Lca Example: Comparing the Carbon Footprint Of Producing Bio...mentioning
confidence: 99%
“…The constantly increasing global concern regarding climate change caused by anthropogenic CO 2 emission has resulted in great attention given to hydrogen as one of the possible solutions [1]. Hydrogen utilization is discussed and slowly implemented in almost every crucial area, e.g., automotive industry [2,3], railway transport [4], household applications [5,6], energy production and storage [7], and heavy industry [8]. In these scenarios, the most-common assumption is that the hydrogen origin is green, meaning it is produced with the use of electrolysis.…”
Section: Introductionmentioning
confidence: 99%